FOOD WASTE: THE ABUNDANCE THAT KILLS BY STARVATION - Biguelini, Thais; Tonél, Rodrigo; Cenci, Daniel Rubens; Dobler, Guilherme Hammarstrom; Gagliardi, André (Salão do Conhecimento, 2017)
Interdisciplinary theme among the areas of law and social sciences.